Pachyonychia congenita type I. Case report. - Grosso, M.; Angelo, C.; Conti, G.; Paradisi, M. (European Journal of Pediatric Dermatology, 2018)
A 6-year-old Columbian child presented markedly thickened toe nails and hyperkeratotic palmar and plantar lesions since birth. A clinical diagnosis of pachyonychia congenita associated with atopia was made. The Authors discuss the diagnostic criteria, the association with other disorders and, finally, the therapeutical problems.